To solve the equation \( 2x - 4x - 3 = -27 \), we first combine like terms on the left side:
\[ 2x - 4x = -2x \]
So the equation simplifies to:
\[ -2x - 3 = -27 \]
Next, we add \( 3 \) to both sides of the equation to isolate the term with \( x \):
\[ -2x - 3 + 3 = -27 + 3 \]
This simplifies to:
\[ -2x = -24 \]
Now, we divide both sides by \( -2 \):
\[ x = \frac{-24}{-2} = 12 \]
Thus, the solution is:
\[ x = 12 \]
Therefore, the correct response from the provided options is:
x = 12 (x equals 12)